Monitoring and Evaluation of Student and Education Elements for Chemistry Undergraduate Program Based on National Accreditation (Monitoring dan Evaluasi Unsur Mahasiswa dan Pendidikan Program Studi Kimia Berbasis Akreditasi Nasional) - La Ode Sumarlin; Nurhasni Nurhasni; Nur Ernita (Shautut Tarbiyah, 2022)
Monitoring and evaluation can help universities to better understand the exchange of information that occurs in their business processes. One of them is student activities and education as well as educational outcomes which are the criteria in the national accreditation process. This also happened to the Chemistry Study Program of UIN Syarif Hidayatullah Jakarta. The results of a literature study through the Academic Information System (AIS) data of UIN Jakarta, field data collection and Focus Group Discussions (FGD) showed that the student element, as well as the balance of the ratio of students to lecturers and education staff, supported the implementation of effective and efficient learning. Elements of education such as policy and curriculum development, curriculum conformity with the field of study program science along with the strengths and advantages of the curriculum, academic culture, learning process, assessment system, and quality assurance system have also been running optimally, but need to be improved. Elements of educational outcomes in aspects of graduate GPA, study period, timely graduation, and study success are quite optimal with a score of 3.68 - 4.00. Elements of student achievement in academic and non-academic fields still need to be improved, especially the aspect of consistency in achievement every year. Meanwhile, elements such as waiting time, suitability of the field of work and the level of satisfaction of graduate users whose scores are still low, need to increase aspects of the number of respondents, the validity of the number of graduates each year, and the quality of implementation of activities.Keywords: Accreditation, Education, Monitoring and Evaluation, Quality Assurance, Student Affairs